miRNAs-19b, -29b-2* and -339-5p Show an Early and Sustained Up-Regulation in Ischemic Models of Stroke - Dhiraj, Dalbir K. (Public Library of Science, 2013)
Stroke, the loss of neurons after ischemic insult to the brain, is one of the leading causes of death and disability worldwide. Despite its prevalence and severity, current therapy is extremely limited, highlighting the importance of further understanding the molecular events underlying ischemia-induced neuronal cell death. An ischemic area can be subdivided into two separate pathophysiological regions: the rapidly dying necrotic core, and the potentially salvageable apoptotic penumbra. Understanding molecular events occurring in the apoptotic ischemic penumbra may give greater insight into mechanisms controlling this salvageable tissue. miRNAs are known to have key roles in the regulation of gene expression in numerous pathological conditions, including the modulation of distinct pathways in stroke. However, previous studies have profiled miRNAs in the whole ischemic infarct, and do not differentiate between miRNA regulation in the necrotic core versus the apoptotic penumbra. We asked if there were unique miRNAs that are differentially regulated following ischemic insults in the salvageable apoptotic penumbra. miRNA expression profiles were compared in the whole infarct from in vivo stroke models, using the three vessel occlusion approach, to an in vitro model of the ischemic penumbra, prior to apoptotic induction. Multiple miRNAs were found to be differentially regulated following ischemic insults in each system. However, miR-19b, miR-29b-2* and miR-339-5p were significantly up-regulated in both model systems. Further, we confirmed these results in a neuroblastoma cell line subjected to a penumbra-like ischemic insult that induced the apoptotic cell death pathway. The data show that miR-19b, miR-29b-2* and miR-339-5p are up-regulated following ischemic insults and may be regulating gene expression to control important cellular pathways in the salvageable ischemic penumbra. Further investigation of their role and mRNA target identification may lead to new insights into the molecular mechanisms taking place in the salvageable apoptotic penumbra.